Evaluating a bioprosthetic anterior mitral valve leaflet made from autologous jugular vein and expanded polytetrafluoroethylene (Gore-Tex) chordae in a sheep model - Janson, Jacques (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.